Case Study on Incentive Mechanism of Energy Efficiency Retrofit in Coal-Fueled Power Plant in China. (16th December 2012) - Yuan, Donghai; Guo, Xujing; Cao, Yuan; He, Liansheng; Wang, Jinggang; Xi, Beidou; Li, Junqi; Ma, Wenlin; Zhang, Mingshun
Abstract : An ordinary steam turbine retrofit project is selected as a case study; through the retrofit, the project activities will generate emission reductions within the power grid for about 92, 463 tCO2 e per annum. The internal rate of return (IRR) of the project is only −0.41% without the revenue of carbon credits, for example, CERs, which is much lower than the benchmark value of 8%. Only when the unit price of carbon credit reaches 125 CNY/tCO2, the IRR could reach the benchmark and an effective carbon tax needs to increase the price of carbon to 243 CNY/tce in order to make the project financially feasible. Design of incentive mechanism will help these low efficiency enterprises improve efficiency and reduce CO2 emissions, which can provide the power plants sufficient incentive to implement energy efficiency retrofit project in existing coal-fuel power generation-units, and we hope it will make a good demonstration for the other low efficiency coal-fueled power generation units in China.